Synthesis and characterization of supported nano Pd-based catalyst for conversion of glycerol to value added chemicals / Norfatehah Basiron - Norfatehah , Basiron (2016)
The abundance bio-availability of glycerol mostly due to biodiesel production, makes it a particularly attractive as feed for the synthesis of value-added chemicals where a series of very important valuable oxygenates can be obtained through selective oxidation of glycerol. The highly selective catalysts are stable for glycerol oxidation to produce valuable chemicals, which potential in industrial manufacturing and environmental applications. There are two main reaction pathways for the oxidation of glycerol, i.e. intermediates via primary hydroxyl or secondary hydroxyl group. The pathway of the reaction is favored by the reaction conditions since glycerol oxidation can occur in acidic or basic pH conditions when using palladium catalyst. The present study, focus on transformation of glycerol to glyceric acid over supported palladium catalysts. Catalyst supports; activated carbon and hydrotalcite were pre-treated and synthesized before adding to the palladium. The three different supported catalysts (1wt% Pd/AC1, 1wt% Pd/HTc and 1wt% Pd/HTc-AC1 were prepared through immobilization method by using poly vinyl alcohol as a surfactant. The catalysts were characterized using TGA, TPR, TPD-CO2, N2 Physisorption, XRD, XRF and HR-TEM for physical and morphological properties. These catalysts were subjected to glycerol oxidation to glyceric acid at mild condition (333 K, 3 bar of O2, 180 minutes and 750 rpm). The obtained results showed better performance of 1wt% Pd/HTc. Further evaluation at various temperature (303-383 K), partial oxygen pressure (1-9 bar), molar ratio NaOH/Glycerol (0-4) showed that 1wt% Pd/HTc catalyst gave the highest conversion of 70.35% and 80.37% selectivity to glyceric acid. Both conversion and selectivity increase with the increase of reaction temperature and pressure. The results also showed that, the conversion increase with increase NaOH/glycerol molar ratio. However, as the NaOH/glycerol, molar ratio exceed two, more side products were generated. Other than that, as the temperature and molar ratio of base/glycerol increased, the selectivity decreases. In summary, oxidation of glycerol mechanism is a dehydrogenation step, hence, the pH of the reaction medium is a crucial factor in this reaction. The temperature plays an important role in glycerol oxidation as palladium metal is non-active at a lower temperature. Furthermore, the influenced of catalyst amount and stirring rate were studied to understand the mass transfer limitation on this reaction. The stability of the catalyst was investigated by filtration experiments and the reaction were re-run three times. The glycerol conversion were reduced from 80.37% to 61.34% for final run suggesting inhomogeneous leaching of palladium could have occurred.